Longitudinal dynamics of intestinal bacteria in the life cycle and their effects on growth and development of potato tuber moth - Qiaosi Fu; Wenqian Wang; Bin Chen; Yuxi Hu; Rui Ma; Enran Zhu; Sitong Jin; Haosheng Cai; Guanli Xiao; Guangzu Du (Frontiers in Microbiology)
Potato tuber moth (PTM), Phthorimaea operculella (Lepidoptera: Gelechiidae), is an oligophagous pest that damages potatoes. Intestinal microorganisms play important roles in regulating the life activities of host insects. The gut of PTM is rich in microbials, but it is unclear that the dynamics of the structure and diversity of intestinal bacteria in the different development period of potato tuber moth. In this study, the dynamics of the intestinal bacterial community across the whole life cycle of PTM were evaluated using single molecule real-time sequencing. The intestinal microbiota of PTM is predominantly composed of Proteobacteria and Firmicutes, and it is different with the difference of development stages. Wolbachia endosymbionts were the dominant species of intestinal symbiotic bacteria in eggs and the first-instar larvae. Enterococcus mundtii was the dominant species of intestinal symbiotic bacteria in the second, third, and the fourth instar larvae, as well as in both male and female pupae. Moreover, the predominant species of intestinal symbiotic bacteria in female adults is Enterobacter ludwigii, while the dominant bacterial species is Serratia rubidaea in male adults. Principal component analysis and non-metric Multi-dimensional scaling analysis confirmed the differences in intestinal symbiotic bacteria structure at different developmental stages. In addition, after reintroducing the bacteria following antibiotic treatment, it was found that the antibiotics significantly inhibited the development of the potato tuber moth, whereas the gut bacteria appeared to facilitate its growth. The findings of this study will enhance our understanding of intestinal microorganisms on the development of their host insects across the life cycle. Moreover, it will establish a foundation for elucidating the physiological functions of key microorganisms in the intestinal tract of the potato tuber moth, while also offering new insights and strategy to the biological control of this pest.